1984
DOI: 10.1038/bjc.1984.77
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the expression of mucus-associated antigens between proximal and distal human colon adenocarcinomas

Abstract: Summary An immunohistological study showed differences in the expression of mucus-associated gastric Ml and intestinal M3 antigens between the proximal (100 cases) and distal (200 cases) colonic adenocarcinomas. Such a regional difference was not observed in the normal colon. A total of 55% and 78% of proximal tumours produced Ml and M3 antigens, respectively (versus 13% and 47%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 13 publications
6
14
0
Order By: Relevance
“…88 Mucinous carcinomas decrease in frequency by approximately 2.5-fold from the proximal to distal colon. 89,90 This is in line with the more frequent expression of mucin-associated M1 antigen in proximal (55%) compared to distal (13%) tumours. 89 Possibly the first report of a site-related molecular difference was the description in 1982 of a progressive increase in the incidence of aneuploidy from proximal to distal tumours.…”
Section: Morphologic and Molecular Differences Between Right And Leftsupporting
confidence: 63%
See 1 more Smart Citation
“…88 Mucinous carcinomas decrease in frequency by approximately 2.5-fold from the proximal to distal colon. 89,90 This is in line with the more frequent expression of mucin-associated M1 antigen in proximal (55%) compared to distal (13%) tumours. 89 Possibly the first report of a site-related molecular difference was the description in 1982 of a progressive increase in the incidence of aneuploidy from proximal to distal tumours.…”
Section: Morphologic and Molecular Differences Between Right And Leftsupporting
confidence: 63%
“…89,90 This is in line with the more frequent expression of mucin-associated M1 antigen in proximal (55%) compared to distal (13%) tumours. 89 Possibly the first report of a site-related molecular difference was the description in 1982 of a progressive increase in the incidence of aneuploidy from proximal to distal tumours. 91 This was followed by evidence for differential expression of the c-myc oncogene and the suggestion that it defined 2 genetically distinct forms of CRC.…”
Section: Morphologic and Molecular Differences Between Right And Leftsupporting
confidence: 63%
“…In contrast, the b and d epitopes were associated with a peak located near the '25I-IgG. DISCUSSION Ml antigens have been identified by their immunohistopathological pattern on human gastrointestinal tract; they have been shown to be associated with the cytoplasm of mucous cells of surface gastric epithelium, and have an oncofetal expression during colon carcinogenesis (Bara et al, 1980(Bara et al, , 1984Decaens et al, 1983). More recently Vol.…”
Section: A~~~0mentioning
confidence: 99%
“…For example, the mucin sulfate content is higher in the distal colon [14], and lectin binding also is site specific [15], As differentiation is lost during the devel opment of malignancy, most distal tumors begin to reexpress the blood group glycopro tein antigens A, B. H, and Leb [16]. In direct contrast, most proximal tumors lose these an tigens, even though they continue to be present in adjoining normal tissue [ 17], These differences also affect the mucin-associated antigens such as M 1 which are expressed w'ith differing frequencies in proximal (55%) and distal (12%) carcinomas [18]. Recent studies in our laboratory have shown significantly more cvclin D1 protein in left-than right sided colon tumors [19].…”
Section: Em Bryology and Geneticsmentioning
confidence: 99%